Analysis Of Factors Affecting Internal Audit Quality With An Understanding Of Information Systems As Moderation Variables - Adam, Rizki Parid (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study aims to examine and analyze the relationship between time budget pressure and auditor competence on the quality of internal audit with an understanding of information systems as a moderating variable at the ministry of finance inspectorate. The method used in this study is a comparative causal research method which aims to determine the causal relationship of the independent variables, namely time budget pressure and auditor competence with the dependent variable, namely the quality of internal audit with the moderating variable understanding of information systems. The research population was 374 people with a sample of 87 people who were determined by purposive sampling technique. Data collection techniques using a questionnaire. Based on hypothesis testing, budget pressure has a positive but not significant effect on the quality of internal audits and auditor competence has a significant positive effect on audit quality. an understanding of the information system as a moderating variable cannot weaken the influence of the budgetary pressure variable on the quality of internal audit and an understanding of the information system as a moderating variable cannot strengthen the influence of auditor competence on the quality of internal audit.